2014
DOI: 10.1186/1471-2458-14-1118
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual hygiene management and school absenteeism among female adolescent students in Northeast Ethiopia

Abstract: BackgroundAdolescence in girls has been recognized as a special period marked with the onset of menarche. Even though menstruation is a natural process, it is associated with misconceptions, malpractices and challenges among girls in developing countries. However, much is not documented; school-absenteeism and dropout are a common problem among girls in rural Ethiopia. Focusing among school girls, this study has examined knowledge about menstruation, determinants of menstrual management and its influence on sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

54
319
11
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(390 citation statements)
references
References 6 publications
54
319
11
6
Order By: Relevance
“…One main problem is the impact of cultural practices and lack of services for menstrual hygiene management on girls' access to education [17]. A study in South India reported that half the girls attending school were withdrawn by their parents once they reached menarche, mostly to be married.…”
Section: Impact On Girls' Educationmentioning
confidence: 99%
“…One main problem is the impact of cultural practices and lack of services for menstrual hygiene management on girls' access to education [17]. A study in South India reported that half the girls attending school were withdrawn by their parents once they reached menarche, mostly to be married.…”
Section: Impact On Girls' Educationmentioning
confidence: 99%
“…As a result girls preferred to stay at home during their menstruation period. [4] The possible role for menstruation in limiting school attendance has received significant attention in popular media, nearly all of which argues that menstruation is likely to be significant factor in schooling. For example, Krist of (2009) writes: "education experts increasingly believe that a cost-effective way to keep high school girls from dropping out in poor countries is to help provide them with sanitary products."…”
Section: World Journal Of Pharmacy and Pharmaceutical Sciencesmentioning
confidence: 99%
“…Dysmenorrhea was significantly associated with school absenteeism and decreased academic performance, sports participation and socialization with peers. [4] Policy advocates for girls" education have suggested there are large losses in schooling due to menstruation and the lack of proper sanitary hygiene in developing countries. This has resulted in media attention and money directed towards sanitary product provision, despite little or no hard evidence on possible impacts.…”
Section: World Journal Of Pharmacy and Pharmaceutical Sciencesmentioning
confidence: 99%
“…In girls, this period as a specific stage of life requires special attention and consideration 2 because the beginning of adolescence is associated, on the one hand, with the onset of puberty and menstruation and, on the other hand, with the discovery of sexual desires 3,4 . Misconceptions and wrong health behaviors in the process of menstruation and puberty endanger the health of girls 5 .…”
Section: Introductionmentioning
confidence: 99%